(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The relevance of this article lies in the fact that central authorities are adopting a number of operational and rapid changes in legislation, as a result of which local self-government bodies have faced difficult challenges associated with unforeseen events. And now there is a need for rational formation, distribution and use of funds from local budgets for the primary needs and consequences of the war. The purpose of this article is to study the peculiarities of the formation and implementation of local budgets under martial law based on the analysis of changes in legislation related to the distribution of local finances during the war in Ukraine. Consideration of the peculiarities of the formation and execution of local budgets during the war period was carried out on the basis of methods of analysis and synthesis. On the basis of the abstract-logical method, a generalization was made and the main measures to improve the formation and execution of local budgets were proposed. To assess the level of filling of local budgets and their expenditures in war and pre-war times, the economic-statistical method and the comparison method were used. The graphic method makes it possible to visually present the data on the basis of which the analysis of income and expenditure of local budgets is carried out. The revenues and expenditures of local budgets for the period January-September 2022 were analyzed. The growth of the share of local budgets in the revenues of the consolidated budget for the period of 2017-9 months of 2022 was revealed. The structure of local budgets’ revenues during the 9 months of 2022 was analyzed, as a result of which it was found that the largest specific weight is occupied by personal income tax. Measures was proposed to improve the formation and implementation of local budgets, namely, to create recovery funds in the budgets and to increase the reserve fund for the reconstruction of territories that suffered during the war, to provide new jobs for potential taxpayers; ensure employment of internally displaced persons, etc. The results of the analysis of the formation and use of funds of local budgets during 9 months of 2022 during martial law testify to the effectiveness of the measures applied by local self-government bodies. The practical value of this article lies in the fact that, based on the analysis, measures are proposed to improve the formation and use of funds from local budgets under martial law.